Effects of etanercept on the apoptosis of ganglion cells and expression of Fas, TNF-α, caspase-8 in the retina of diabetic rats - Ye, Qin (Int J Ophthalmol, 2019)
AIM: To evaluate the effects of etanercept on the expression of Fas, tumor necrosis factor-alpha (TNF-α) and caspase-8 in the early stage of the apoptotic pathway in diabetic rats, and to explore the therapeutic effect of etanercept on diabetic retinopathy. METHODS: A total of 60 Sprague-Dawley (SD) rats were randomly and evenly divided into 3 groups with 20 rats each, including control group, and diabetic groups with or without treatment. Streptozotocin (STZ)-induced diabetic rats were established for diabetic groups. Blood glucose and body weight were measured weekly. All the rats were sacrificed at the 12wk after treatment. The expressions of Fas, TNF-α and caspase-8 in rat retina were quantitatively detected by PCR and Western blot. The leakage of Evan blue was adopted to measure the retinal vascular leakage quantitatively, and to compare it among different groups. TUNEL method was used to compare the amount of apoptotic bodies quantitatively in rat retina ganglion cells under electron microscope. RESULTS: The expressions of Fas, TNF-α and caspase-8 in each group were compared via PCR and Western blot, in which the diabetic group with treatment was lower than those without treatment (P<0.01), but all the diabetic groups were higher than the control group (P<0.01). Evans blue leakage in the diabetic treatment group was lower than those without treatment (P<0.01), but those in the control group was the lowest compared with the other two groups (P<0.01). TUNEL method showed that the apoptotic bodies of retina in the diabetic treatment group was lower than those without treatment (P<0.01), while those in the control group was the lowest compared with the other two groups (P<0.01). CONCLUSION: Etanercept can effectively reduce the expression of Fas, TNF-α and caspase-8, as well as the retinal leakage and retinal cell apoptosis in diabetic rats.